Interaction between arteriosclerosis and the APOE4 gene in cognitive decline in older adults: a cross‐sectional study in rural minority areas in western China. Issue 2 (19th January 2022) - Qu, Fang; Yang, Xing; Yang, Jingyuan; Zhou, Quanxiang; Yang, Xi; Chen, Mingyan; Xiong, Yan; Hu, Yuxin
Abstract : Background: Numerous studies have confirmed that the apolipoprotein E4 allele ( APOE4 ) gene and arteriosclerosis (AS) have a combined effect on the occurrence of cognitive function impairment, and dyslipidaemia levels are significantly correlated with APOE4 levels and AS. Few studies have focused on the combined effect of the APOE4 gene and AS on cognitive function. Therefore, this study aimed to investigate the effect of APOE4 gene and AS acting together on cognitive function through dyslipidaemia levels, which could provide certain scientific research value for future studies. Methods: A multi‐stage cluster sampling method was used to investigate older adults aged 60 years and above in rural areas of Guizhou, China. The demographic sociological characteristics were collected, and laboratory tests, blood lipid measurements, and physical examinations were performed. Mini‐Mental State Examination (MMSE) was used to determine cognitive function. Analysis of variance with two‐factor factorial design was used to analyse the interaction between the APOE4 gene and AS on cognitive function and its domains. Results: A total of 549 elderly subjects were eligible for this study. The result of the factorial design analysis revealed there was a significant interaction between the APOE4 gene and AS in terms of attention and numeracy ( F = 6.878, P = 0.009). Conclusions: The combination of the APOE4 gene and AS leads to a decrease in the level of attention and numeracy domains, and certain attention should be focused on such populations in the future.